2D and 3D numerical modelling of flow through composite liners involving partially saturated GCLs. Issue 6 (1st December 2006) - Goblet, P.; Saidi, F.; Touze-Foltz, N.
Abstract : A numerical study was performed in order to investigate the influence on the flow rate of the presence of defects in the geomembrane of a composite liner involving GCLs. In the approach presented in this paper, porous media in the composite liner, i.e. the interface, the GCL and the underlying soil liner, which is a CCL, are partially saturated in the numerical modelling performed. The first aim of the paper is to evaluate the impact of this partial saturation on the flow rates and the lateral extension of the wetted area for circular defects and defects of infinite length in the geomembrane through 2D numerical modelling. Results from existing analytical solutions are used as a reference. Results obtained in terms of flow rates and wetted areas reveal that: (i) a good agreement is obtained as regards flow rates between numerical modelling and analytical solutions; and (ii) larger differences between numerical and analytical results were observed for the wetted area, attributed to the difference in saturation state in both cases. The second aim of the paper is to check the impact of the shape of the ends of defects of finite length – circle or square – and to test the impact of 2D and 3D modelling of this end on the resulting flow rates. Results obtained show that the impact on the flow rate of the shape of the ends is negligible. However, 2D and 3D modelling can lead to significantly different results depending on the defect length, especially as regards the evolution of the flow rate with the hydraulic head.